The catching fire : the second book of the hunger games - Collins, Suzanne (New York : Scholastic Press, 2022)
Celebrate the 10th anniversary of The Hunger Games Trilogy with this collectible paperback boxed set featuring new foil covers for all three books in the series -- The Hunger Games, Catching Fire, and Mockingjay. It will feature The Hunger Games Special Edition, which includes more than 50 pages of new bonus material, including the most extensive interview Suzanne Collins has given since the publication of The Hunger Games, featuring an absorbing behind-the-scenes look at the creation of the series; an engaging archival conversation between Suzanne Collins and YA legend Walter Dean Myers on writing about war; and a timeline of highlights from the first ten years of The Hunger Games. The extraordinary, ground breaking New York Times bestsellers The Hunger Games and Catching Fire, along with the third book in The Hunger Games trilogy by Suzanne Collins, Mockingjay, are available in a beautiful boxset edition.
Keywords: Children's Science Fiction; Dystopian Sci-Fi Books for Young Adults; Young Adult Fiction on Physical & Emotional Abuse